Agricultural landscape modification and land food footprint from 1970 to 2010: A case study of Sardinia, Italy. (1st December 2019) - Lombardi, Ginevra Virginia; Atzori, Rossella; Acciaioli, Anna; Giannetti, Biagio; Parrini, Silvia; Liu, Gengyuan
Abstract: Urban population growth has caused significant changes in rural areas, leading to landscape modifications. These modifications affect rural systems via different mechanisms linked to alterations in land use, loss of landscape biodiversity, and habitat destruction. All these mechanism are set in motion by higher levels of global food demand, which requires increasing yields through high-input, specialised agriculture. Consequently, local food systems and food security are increasingly dependent by global food production, trade and transport. The Land Food Footprint is a suitable tool for assessing the evolution of food systems and land displacement, whereas the Shannon, Dominance and Sharpe landscape indexes jointly implemented with indicators of human disturbance and of proportion of natural area allow us to assess landscape modification and its impact on agricultural resources. In this study, we analysed the evolution of land food footprint and landscape changes in Sardinia over the period of 1970–2010 to assess whether land displacement implies landscape modifications. We also evaluated whether landscape modification entails an intensified use of resources and involves enacting changes in regional capability to satisfy the food needs of the local population. In the time series, results of landscape quantitative analysis indicate that the decrease in land food footprint balance is paired with landscape changes with a greater degree of dominance of few land uses due to agricultural specialisation in animal husbandry and abandon of marginal, less suitable and less profitable production areas. The reduced diversity of locally produced food due to the modification of food production and consumption systems is linked to modifications in traditional landscape with implications on local resources conservation. The regional land unbalance and the reduction in agricultural land capacity to support the local population food demand underline the need for food planning in the future. Highlights (RA): This study underlines the connection between landscape modification and agri-food systems. Sardinia available land is enough to satisfy the regional consumption of considered food, but the land balance decreases from 1970 to 2010. The landscape modification implies a reduction in agricultural land capacity to support the local population food needs. The consumption of locally produced food protects landscape and ecosystem values and promotes local development revitalizing rural areas.